Photosynthetic responses of heat-stressed apple leaves to foliar application of salicylic and ascorbic acid - Mihaljević, I; Viljevac Vuletić, M; Tomaš, V; Zdunić, Z; Vuković, D (Photosynthetica, 2024)
High temperatures have significant impacts on fruit tree production. Foliar spraying application of promoting agents can be a sustainable approach to managing high-temperature stress in orchards. The mechanism of certain improving agents on photosynthesis is not yet well understood, particularly in fruit trees. Photosynthesis, as a vital and very sensitive process in plants, is a pivotal component in fruit production. Therefore, in this study, we explored the potential of two different promoting agents, salicylic acid (SA) and ascorbic acid (AsA), to alleviate oxidative stress caused by high temperature in controlled conditions (37°C for 1 h) at the photosynthetic level. For studying photosynthetic responses, we used chlorophyll fluorescence measurements. According to our findings, foliar application of promoting agents effectively increased the high-temperature tolerance of apple leaves, when compared to sole heat stress treatment. Both promoting agents significantly increased photosynthetic efficiency under stress, while the maximum was observed with AsA. In general, AsA and SA applications had a positive effect on the photosynthesis of apple leaves at high temperatures.
Keywords: high temperature; chlorophyll content; electron transport chain; photosystem II; chlorophyll a fluorescence